2018
DOI: 10.3390/app8081375
|View full text |Cite
|
Sign up to set email alerts
|

Mg-Based Hydrogen Absorbing Materials for Thermal Energy Storage—A Review

Abstract: Utilization of renewable energy such as solar, wind, and geothermal power, appears to be the most promising solution for the development of sustainable energy systems without using fossil fuels. Energy storage, especially to store the energy from fluctuating power is quite vital for smoothing out energy demands with peak/off-peak hour fluctuations. Thermal energy is a potential candidate to serve as an energy reserve. However, currently the development of thermal energy storage (TES) by traditional physical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 82 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…In the present paper, magnesium iron hexahydride (Mg2FeH6) has the highest value density (Table 1). This latter complex transition-metal hydride, recently synthesized in its pure state [44], has attracted great attention due to its high stability compared with MgH2 and its highest volumetric hydrogen density (150 kg/m 3 ), in addition to the large abundance and low cost of iron and magnesium [55][56][57][58][59]. Table 4 displays the calculated 𝐼 𝑠𝑝,𝑣 delivered by three AP/HTPB propellants at optimal compositions.…”
Section: Theoretical Volumetric Specific Impulsementioning
confidence: 99%
“…In the present paper, magnesium iron hexahydride (Mg2FeH6) has the highest value density (Table 1). This latter complex transition-metal hydride, recently synthesized in its pure state [44], has attracted great attention due to its high stability compared with MgH2 and its highest volumetric hydrogen density (150 kg/m 3 ), in addition to the large abundance and low cost of iron and magnesium [55][56][57][58][59]. Table 4 displays the calculated 𝐼 𝑠𝑝,𝑣 delivered by three AP/HTPB propellants at optimal compositions.…”
Section: Theoretical Volumetric Specific Impulsementioning
confidence: 99%
“…Therefore, TCHS based on reversible chemical reaction is considered as a potential heat storage technology. The common heat storage materials in the TCHS system are hydrides (e.g., Mg/MgH 2 ), metal hydroxide (e.g., MgO/Mg­(OH) 2 ), metal redox (e.g., Mn 2 O 3 /Mn 3 O 4 ), and carbonates (e.g., CaO/CaCO 3 ). The CaO/CaCO 3 TCHS system is a promising candidate in CSP plants due to its high safety, high energy density, and widespread availability .…”
Section: Introductionmentioning
confidence: 99%
“…In TES systems, Mg‐based phase change heat storage alloy has the advantage of low corrosion at high temperatures, which are better than Al‐based alloys in comparison. Currently, researchers have focused more on the Mg‐based phase change heat storage alloy as TES materials, and have conducted a lot of research 19‐24 . For instance, Faik et al 25 investigated the structure and thermophysical properties of Zn 85.8 Al 8.2 Mg 6 and Mg 70 Zn 24.9 Al 5.1 eutectic alloys, and found that the great potential of the alloys studied in heat energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers have focused more on the Mg-based phase change heat storage alloy as TES materials, and have conducted a lot of research. [19][20][21][22][23][24] For instance, Faik et al 25 investigated the structure and thermophysical properties of Zn 85.8 Al 8.2 Mg 6 and Mg 70 Zn 24.9 Al 5.1 eutectic alloys, and found that the great potential of the alloys studied in heat energy storage applications. Fang et al 26 calculated Mg-Bi phase change alloy as TES material and found that Mg-54%Bi alloy has high melting enthalpy and activation energy, among which the activation energy is as high as 1322.8 kJÁmol −1 .…”
Section: Introductionmentioning
confidence: 99%